2020
DOI: 10.1523/eneuro.0189-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of nAChRs and Changes in Excitability on VTA Dopamine and GABA Neurons Correlates to Changes in Nicotine-Reward-Related Behavior

Abstract: Upregulation of nAChRs and changes in excitability on VTA dopamine and GABA neurons correlates to changes in nicotine-reward related behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…We have previously shown that nicotine reward-related behavior correlates with the degree of α4-containing (α4*) and α4α6* nicotinic acetylcholine receptor (nAChR) upregulation. 10 We have also previously observed that pharmacological agents that enhance nicotine reward-related behavior also enhance nAChR upregulation. 11 Accordingly, we examined the impact of nicotine, morphine, and their combination on reward, reinforcement, and nAChR upregulation in the ventral tegmental area (VTA).…”
Section: Introductionmentioning
confidence: 90%
“…We have previously shown that nicotine reward-related behavior correlates with the degree of α4-containing (α4*) and α4α6* nicotinic acetylcholine receptor (nAChR) upregulation. 10 We have also previously observed that pharmacological agents that enhance nicotine reward-related behavior also enhance nAChR upregulation. 11 Accordingly, we examined the impact of nicotine, morphine, and their combination on reward, reinforcement, and nAChR upregulation in the ventral tegmental area (VTA).…”
Section: Introductionmentioning
confidence: 90%
“…In the IPN, chronic nicotine exposure results in increased α5 transcript levels only in females, while α7 transcript was increased only in males ( Correa et al, 2019 ). Another recent report utilized mice with fluorescently tagged α4 and α6 nAChR subunits to measure receptor expression in the VTA following nicotine conditioned place preference, finding no sex differences in the degree of α4 ∗ and α4α6 ∗ nAChR upregulation ( Akers et al, 2020 ).…”
Section: Sex Differences In Nicotinic Acetylcholine Receptor Expression and Regulationmentioning
confidence: 99%
“…Nicotine mediates its psychoactive effect by acting on nicotinic acetylcholine receptors (nAChRs) in the brain. Within the mesolimbic circuit, including ventral tegmental area dopamine neuron projections to nucleus accumbens, activation of nAChRs contribute to the rewarding effect of nicotine (Akers et al, 2020;Calabresi et al, 1989;Grieder et al, 2019;Liu et al, 2012;Mansvelder & McGehee, 2000;Peng et al, 2017;Pons et al, 2008;Pontieri et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine mediates its psychoactive effect by acting on nicotinic acetylcholine receptors (nAChRs) in the brain. Within the mesolimbic circuit, including ventral tegmental area dopamine neuron projections to nucleus accumbens, activation of nAChRs contribute to the rewarding effect of nicotine ( Calabresi et al, 1989 ; Pontieri et al, 1996 ; Mansvelder and McGehee, 2000 ; Pons et al, 2008 ; Liu et al, 2012 ; Peng et al, 2017 ; Grieder et al, 2019 ; Akers et al, 2020 ). Conversely, the excitatory projection from medial habenula (MHb) to interpeduncular nucleus (IPN) has been identified as a key substrate on which nicotine actions contribute to nicotine aversion ( Salas et al, 2009 ; Fowler and Kenny, 2011 , 2014 ; Fowler et al, 2011 ; Frahm et al, 2011 , 2015 ; Antolin-Fontes et al, 2015 , 2020 ; Tuesta et al, 2017 ; Elayouby et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%